Desain dan Struktur Organisasi Manajemen Pendidikan yang Efektif di Perguruan Tinggi - Hesti Kusumaningrum; Iffat Bening Qhuru’in Ahmad; Inu Aulia Arba (Pendidikan Al-Gafari, 2024)
Organizations are a very important element in modern society both in the public sector (State) and in the private sector. Each organization has certain boundaries, so that someone who interacts with other parties is not of their own free will, they are limited by certain rules. Therefore, each organization has a different structure that can affect the attitudes and behavior of its members. To achieve these goals, higher education institutions need a good organizational structure, namely a healthy and efficient organizational structure. organizational structure is the result of the management process, in this case as the output of the organizing process. In the process of forming an organizational structure, the Team must pay attention to and apply various organizational principles, namely the formulation of clear objectives, departmentalization, division of labor, delegation of authority, span of control, organizational levels, and unity of command. The application of these principles in the organizing process can result in a healthy and efficient organizational structure.